Food Insecurity and Sleep Disturbance Among 223,561 Adolescents: A Multi-Country Analysis of Cross-Sectional Surveys - Wang, Qiuying (Frontiers in Public Health, 2021)
This study was to investigate the association between food insecurity (FI [hunger]) and sleep disturbance in adolescents from 68 countries. Cross-sectional data from the Global School-based Student Health Survey were analyzed. Data on FI and sleep disturbance were collected using a self-reported questionnaire. Multivariable logistic regression and meta-analysis were conducted to assess the association between FI and sleep disturbance. The final sample consisted of 223,561 adolescents. The prevalence of severe FI and sleep disturbance were 6.4% and 8.0%, respectively. After adjustment for potential confounders, severe FI was significantly associated with higher odds for sleep disturbance in 48 of the 68 countries studied, with the pooled OR (95% CI) being 1.94 (1.79-2.09). Overall, the associations were similar across countries and gender. But there was a large level of heterogeneity in the associations across upper- and middle-income countries. FI is a global problem and is associated with sleep disturbance. The identification of adolescents suffering from FI and remedying this condition may be important to improve sleep quality among adolescents worldwide.